PENGARUH CITRA MEREK DAN KUALITAS LAYANAN TERHADAP KEPUASAN PELANGGAN INDOVISION DI SEMARANG - Sholekatun Fadhilah, 09.05.51.0022; Tjahjaningsih, Endang (Students Journal of Economic and Management, 2013)
Indovision is a company engaged in television service in Indonesia, which has been trying to provide good service to its customers so that customers feel satisfied, but there are indications of a decline in customer satisfaction can be seen from the falling percentage of the number of customers. Matters relating to customer satisfaction such as brand image and service quality. This study aimed to determine the effect of brand image and service quality on customer satisfaction Indovision Semarang branch, either partially or simultaneously.Â The population in this study were all customers Indovision Branch Semarang, the sampling technique used is accidental sampling. Data collection is done through a questionnaire. Data analysis was performed by multiple regression but first tested the validity and reliability data analysis of the data using a parcial hypothesis test (ttest), simultaneous testing (Test f) and the coefficient of determination (R2). Based on the analysis conducted showed that brand image has a positive and significant effect on customer satisfaction with a significancevalue of 0.011 which is smaller than 0.05, the quality of service also has a positive and significant effect on customer satisfaction with a significant value of 0.000 which is smaller than 0.05 . While simultaneously brand image and service quality has positive and significant impact on customer satisfaction with a significance value of 0.000 is smaller than 0.05. Brand image and service quality affects customer satisfaction Indovision Semarang branch of 85%. The quality of service has a greater influence than the brandi mageto customer satisfaction. The conclusion of this research is that the brand image and service quality has a positive and significant impact on customer satisfaction either partially or simultaneously. Suggestions can be submitted Indovision management should create a program that can create a positive image to the community. Maintain and enhance the quality ofservice that customers feel more comfortable and loyal to Indovision.Key words : brand image,service qualitv and customer satisfaction